(untitled) (Journal of Hama University, 2021)
The aim of this research was to identify the economic and social characteristics of dray onion producers in Salamiah City-Hama Governorate. It also aimed to define the nature of the relationship between the productivity of the studied crop and the economic and social characteristics of farmers. The results of the production function estimation showed that three independent variables, namely the amount of organic fertilizer and the number of seeds and irrigation water costs, have been explained (89%) the change in the yield of dunums of onion. The estimated significance of the estimated F has also been proven, as it was found that the elasticity coefficient of production was estimated at (0.37), (2), (1.3), and the total elasticity coefficient reached about (3.40), and that the economic return of the unit used from the aforementioned productive elements is estimated at (64.36), (25.24), (232.5) for each of the organic fertilizer and the number of seeds and irrigation water costs Respectively.